Nelson's syndrome. - Barber, T; Adams, E; Ansorge, O; Byrne, J; Karavitaki, N; Wass, J (2010)
Nelson's syndrome is a potentially life-threatening condition that does not infrequently develop following total bilateral adrenalectomy (TBA) for the treatment of Cushing's disease. In this review article, we discuss some controversial aspects of Nelson's syndrome including diagnosis, predictive factors, aetiology, pathology and management based on data from the existing literature and the experience of our own tertiary centre. Definitive diagnostic criteria for Nelson's syndrome are lacking. We argue in favour of a new set of criteria. We propose that Nelson's syndrome should be diagnosed in any patient with prior TBA for the treatment of Cushing's disease and with at least one of the following criteria: i) an expanding pituitary mass lesion compared with pre-TBA images; ii) an elevated 0800 h plasma level of ACTH (>500 ng/l) in addition to progressive elevations of ACTH (a rise of >30%) on at least three consecutive occasions. Regarding predictive factors for the development of Nelson's syndrome post TBA, current evidence favours the presence of residual pituitary tumour on magnetic resonance imaging (MRI) post transsphenoidal surgery (TSS); an aggressive subtype of corticotrophinoma (based on MRI growth rapidity and histology of TSS samples); lack of prophylactic neoadjuvant pituitary radiotherapy at the time of TBA and a rapid rise of ACTH levels in year 1 post TBA. Finally, more studies are needed to assess the efficacy of therapeutic strategies in Nelson's syndrome, including the alkylating agent, temozolomide, which holds promise as a novel and effective therapeutic agent in the treatment of associated aggressive corticotroph tumours. It is timely to review these controversies and to suggest guidelines for future audit.